Pro-inflammatory cytokines gene expression in liver and kidneys of rats exposed to a sub-lethal dose of Bitis arietans snake venom: Inflammatory cytokines expression by snake venom - Khan, Haseeb A.; Abdulnasir, Anwar J.; Alamery, Salman; Altwaijry, Nojood A.; Ibrahim, Khalid E. (Cellular and Molecular Biology, 2024)
Bitis arietans (Puff adder) is a poisonous snake and its bite causes pain, edema, blistering, tissue damage and neutrophilia. There are limited studies on inflammatory process involved in Bitis arietans envenomation. We therefore investigated the role of proinflammatory cytokines in Bitis arietans venom (BAV)-induced liver and kidney toxicities in rats. Adult male Sprague Dawley rats were treated with BAV (0.5 mg/kg) and were sacrificed after specific time intervals (2 h, 24 h, 1 week). Blood samples were collected for liver and renal function tests and tissues were collected for histopathology and gene expression analysis of IL-1β, IL-6, and TNF-α in liver and kidneys. There was no significant difference in serum ALT activities among different treatment groups. Serum AST was significantly increased at 24 h following BAV injection. In both organs, injection of BAV resulted in mild inflammatory cell infiltration at 2 h post-dosing which normalized after 1 week. In liver, there was a significant increase in IL-1β expression in BAV-treated rats at 2 and 24 h post-dosing that reduced after one week. Significant increases in IL-6 and TNF-α were observed at 24 h and 1 week after BAV exposure. In kidneys, there were significant increases in IL-1β and TNF-α expression at 24 h that subsided after 1 week. In conclusion, a single sub-lethal dose of BAV caused an acute phase inflammation in liver and kidneys. It is most probable that a higher dose of BAV may result in greater and irreversible damage to these organs.